Duality for set-valued multiobjective optimization problems. Part 2: Optimal control - Azimov, A. Y. (SPRINGER/PLENUM PUBLISHERS, 2008)
The present paper is a continuation of a paper by Azimov (J. Optim. Theory Appl. 2007, accepted), where we derived duality relations for some general multiobjective optimization problems which include convex programming and optimal control problems. As a consequence, we established duality results for multiobjective convex programming problems. In the present paper (Part 2), based on Theorem 3.2 of Azimov (J. Optim. Theory Appl. 2007, accepted), we establish duality results for several classes of multiobjective optimal control problems.
Keywords: duality in multiobjective optimization; duality for multiobjective optimal control problems; convexity of the set of vector integrals; minimax theorems; multiobjective quasilinear optimal control problems; PROPER EFFICIENCY; Operations Research & Management Science; Mathematics